From pilots to policy: upscaling sediment management strategies for climate resilience in a transboundary estuary - Richard J.C. Marijnissen; Yuting Tai; Sara P. Cobacho; Martin J. Baptist; Dirk S. van Maren; Pushpa Dissanayake; Dennis Oberrecht; Dirk Post; Matthijs Buurman; Jantsje M. van Loon-Steensma; Wei Chen; Joanna Staneva; et al. (Ocean & Coastal Management, 2026)

A new era for science-industry research collaboration – a view towards the future - Matthew R. Baker; Nathalie A. Steins; Martin A. Pastoors; Stefan Neuenfeldt; Andries de Boer; Dirk Haasnoot; Stephanie Madsen; Johan Muller; Kobus Post; Claus R. Sparrevohn; Mart van der Meij (Frontiers in Marine Science, 2023)
Direct engagement of the fishing industry in the provision and co-creation of knowledge and data for research and management is increasingly prevalent. In both the North Atlantic and North Pacific, enhanced and targeted engagement is evident. More is needed. Science-Industry collaborative approaches to developing questions, collecting data, interpreting data, and sharing knowledge create opportunities for information transfer and improved understanding of ecosystem interactions, stock dynamics, economic incentives, and response to management. These collaborations require clear communication and awareness of objectives and outcomes. These initiatives also require careful attention to conditions and interactions that foster respect, trust, and communication. Respect is critical and entails acknowledging the respective skills and expertise of both scientists and fishers. Trust is needed to build confidence in the information developed and its use. Communication is essential to maintain relationships and leverage shared insights. To assess current trends and future opportunities related to this type of engagement, we convened a networking session of research scientists, industry scientists, industry leaders, and fishers at the Annual Science Meeting of the International Council for the Exploration of the Sea (ICES) to address the following questions: (1) What are scientific needs that could be addressed with industry-collected data or knowledge? And (2) How can science-industry collaboration be made sustainable? Here we identify opportunities and acknowledge challenges, outline necessary conditions for respectful and sustainable collaborative research, and highlight ways to promote stakeholder involvement in developing science. We address industry concerns and solicit industry advice. We also address challenges to scientists in ensuring standards for scientific data, conflict of interest, and applying information to advise management. The discussions in this session and subsequent correspondence have led to a set of guidelines and best practices that provide a framework to advance further collaboration between industry and research science. We identify opportunities for directed engagement. We also detail potential approaches to clarify expectations and develop avenues for iterative communication and engagement to sustain collaborative efforts over time. The intent is to improve and expand data streams and contextual understanding of ecosystem processes, stock assessment, and socio-economic dynamics to the benefits of science and industry alike.